Optimization of the work environment and observance of work discipline in improving employee performance - Andriyani, Desi; Muspiroh, Sinta; Aini, Siti Nurul; Haryadi, Didit; Wahyudi, Wahyudi (Trigin Publisher, 2024)
Employee performance is an important factor influencing success. In an organization, this is one of the most important functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used the associative descriptive quantitative method with a population of 36 respondents drawn into samples using non-probability sampling using saturated sampling / total sampling methods. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis of the work environment has a significant effect on employee performance. Thus, the second hypothesis states that work discipline significantly influences employee performance. The third hypothesis is that employee performance is influenced by the work environment and work discipline, which can simultaneously improve and accelerate the improvement of employee performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.